Optimizing Self-Acceptance in Mothers with Children with Down Syndrome Through a Reality Counseling Approach - Putri, Andissa Layyanah (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2023)
Mothers often experience profound sadness upon learning that their child has Down syndrome. The initial reactions include denial, shock, disbelief, and shame, which can lead to low self-acceptance, such as self-blame and refusal to accept the current situation. This research aims to increase self-acceptance in mothers with children who have Down syndrome through reality counseling (konseling realitas). The research uses a qualitative approach, with data collection methods including observation, interviews, and documentation. The reality counseling was conducted over four stages within six weeks. The results of this study indicate that reality counseling can effectively improve self-acceptance in mothers with children who have Down syndrome. This finding suggests that this counseling approach can assist mothers in adapting to their situation and improving their emotional well-being, which ultimately supports better parenting